Проблема свободы и ответственности в информационной среде - Шляхтун, М. М. (ХНУРЭ, 2012)
This work tries to figure out where is a place of liberty and responsibility in an information environment which arise in modern world in consequence of globalization and information activity in XXI century in conjunction with human and its reflection in such environment.